ChemInform Abstract: La2NiSb — A Ternary Ordered Version of the Bi3Ni Type with Highly Polar Bonding. Issue 12 (March 2015) - Schaefer, Konrad; Isaeva, Anna; Ruck, Michael; Gerke, Birgit; Schwickert, Christian; Poettgen, Rainer
Abstract La2NiSb is prepared by annealing a cold‐pressed pellet of the elements (evacuated silica tube, 1120 K, 500 h).